A Peripherally Inserted Central Catheter is a Safe and Reliable Alternative to Short-Term Central Venous Catheter for the Treatment of Trauma Patients - Dong Yeon Ryu; Sang Bong Lee; Gil Whan Kim; Jae Hun Kim (Journal of Trauma and Injury)
Purpose To determine whether a peripherally inserted central catheter (PICC) meets the goals of a low infection rate and long-term use in trauma patients. Methods From January 2016 to June 2018, the medical records of patients who underwent central venous catheterization at a level I trauma center were retrospectively reviewed. Data collected included age, sex, injury severity score, site of catheterization, place of catheterization (intensive care unit [ICU], emergency department, or general ward), type of catheter, length of hospital stay during catheterization, types of cultured bacteria, time to development of central line-associated bloodstream infection (CLABSI), and complications. Results During the study period, 333 central vein catheters (CVC) were inserted with a total of 2,626 catheter-days and 97 PICCs were placed with a total of 2,227 catheter-days. The CLABSI rate was significantly lower in the PICC group when the analysis was limited to patients for whom the catheter was changed for the first time in the ICU after CVC insertion in the ER with similar indication and catheter insertion times (18.6 vs. 10.3/1,000 catheter-days, respectively, p<0.05). The median duration of catheter use was significantly longer in the PICC group than in the CVC group (16 vs. 6 days, respectively, p<0.05). Conclusions The study results showed that the duration of catheter use was longer and the infection rate were lower in the PICC group than in the CVC group, suggesting that PICC is a safe and reliable alternative to conventional CVC.